A CONTENT ANALYSIS OF ENGLISH TEXTBOOK â€œWHEN ENGLISH RINGS A BELLâ€ FOR EIGHTH GRADE STUDENT OF JUNIOR HIGH SCHOOL - Yayang Prisilia; Efransyah Efransyah (PROJECT (Professional Journal of English Education), 2023)
The purpose of this study was to assess the applicability of the eighth-grade English textbook â€œWhen English Rings a Bellâ€ to the 2013 curriculum. This research employed a qualitative method known as document analysis. This textbook had eleven chapters, of which the researcher studied five. The researchers conducted the research instrument, and data were collected using the 2013 English textbook and curriculum outline. According to the findings, 16 of the bookâ€™s components, or 68.41 percent, are relevant, two are partially relevant with 17.40 percent, and three are irrelevant with 14.19 percent. Based on these data, the researchers concluded that the textbook appropriately addresses the topicâ€™s objectives, linguistic characteristics, and social functions. Based on the data, it can be determined that the textbook covers 68.41 percent of the cognitive domainâ€™s material relevancies and is capable of meeting the learning objectives, language aspects, and social functions of the ideal materials intended for the students.Â Keywords:Â  Content Analysis; Textbook; Cognitive Domain